Environmental Management Systems as soruces of competitive advantage - Knud Sinding (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2001)
An increasing number of firms are adopting environmental management systems as a way of dealing with challenges from the natural environment. Many of these firms also decide to have their environmental management systems certified according to one or both of the available international standards, ISO 14001 and EMAS (The European Unions Eco Management and Audit Scheme). Both the environmental management system and the certification process involve significant investment of financial resources and management effort, which raises the question of what benefits firms might derive from these activities. Three levels of strategic advantage are identified in this paper. The first level of advantage is transient on nature, being based on competitive preemption and development of first mover advantage. The second level involves development of valuable competencies and more durable resources inside the firm, while the third level advantage depends on the extent to which such resources can be extended and conserved when emphasis shifts from an internal pollution prevention focus towards life cycle oriented environmental management.
Keywords: 330; Natural environment; strategy; resource-based view; Umweltmanagement; Wettbewerbsvorteil